EFFECT OF DIFFERENT TYPES AND LEVELS OF PHOSPHATE FERTILIZERS ON GROWTH AND YIELD FOR TWO VARIETIES OF WHEAT (Triticum aestivum) - Fatih Hasen (Mesopotamia Journal of Agriculture)
A pots experiment was carried out under plastic house conditions to study the effects of two levels of phosphorus (160 kgP2O5 ha-1, 320 kgP2O5 ha-1) in the form of RP, TSP, DAP, and NP on vegetative growth, yield and N, P, K content in seed of two varieties of wheat (Sham-4, Um rabie) grown in calcareous soil in the north part of Iraq. The results showed that the addition of phosphorus caused a significant increase on most vegetative growth parameters (dry matter, plant height, number of tiller), yield components (number of  spikes, Weight of 1000 grain and grain yield) in the two wheat varieties. and also increased the contents of N, P  and K  in the seeds of the two varieties. Treatment of 320 kg P2O5ha-1 as TSP showed better results as compared to RP, DAP and NP.